Epidermal growth factor reduces multiorgan failure induced by thioacetamide. Issue 1 (1st January 2001) - Caballero, M E; Berlanga, J; Ramirez, D; Lopez-Saura, P; Gozalez, R; Floyd, D N; Marchbank, T; Playford, R J
Abstract : BACKGROUND: Multiorgan failure is a severe life threatening state where present therapeutic approaches are suboptimal. Epidermal growth factor (EGF) is a potent stimulant of repair in in vitro and in vivo models. We therefore examined its potential beneficial effect in reducing mortality and injury induced by the noxious agent thioacetamide (TAA). METHODS: Mice (20 per group) were fasted overnight and received a single intraperitoneal dose of human recombinant EGF at 10 or 30 μg/kg or saline (control). Either 30 minutes before or after EGF, all animals also received TAA (40 mg/kg intraperitoneally). Twenty four hours later, surviving animals were killed, tissues collected, and degree of organ injury assessed. RESULTS: Fifty per cent (10/20) of control animals died within the first 24 hour period. Mortality was almost completely prevented by the higher dose of EGF whether given before or after TAA (p<0.01) and was reduced by about 50% with the lower dose of EGF. In control animals, the entire length of the jejunum and ileum had necrosis with or without mucosal denudation. In contrast, necrosis affected only about 10–20% of the total length in EGF treated groups (both p<0.01 v control). Control animals showed marked glomerular tuft collapse, interstitial haemorrhage, and increased plasma creatinine levels. These effects were significantly reduced in animals given EGF (30 μg/kg; p<0.01). All groups showed similar changes in liver histology (centrilobular necrosis) and alanine transaminase levels (10-fold increase). CONCLUSIONS: Although EGF did not prevent the hepatotoxicity associated with TAA, it reduced mortality, renal injury, and gastrointestinal damage. These studies provide preliminary evidence that EGF may be a novel approach for the prevention and/or treatment of multiorgan failure.